RESEARCH OF PROPERTIES OF SEDIMENTS FORMED IN COURSE OF WHEY AND ITS CONCENTRATES SEPARATION - E. A. Chebotarev; A. D. Lodygin (Современная наука и инновации, 2022)
Five types of protein precipitate can be obtained in the course of whey and its concentrates separation, which, in turn, are divided into precipitates derived from cheese and curd whey. The main factors affecting the moisture content in the sediment are: structural properties, the magnitude of the centrifugal sealing pressure, separation temperature and compaction time. As shown by studies of sediment samples obtained during the separation of whey and its concentrates, their structural properties are quite similar. The properties of various protein sediments were experimentally determined: the dependence of humidity on sealing pressure, the influence of strain rate on the coefficient of effective viscosity valuation. The data obtained can be used for mathematical modeling of the centrifugal unloading of sediment. An experimental modeling of the sediment behavior on the conical surface of the slurry space was carried out, on the basis of which the limiting angle of inclination of the conical surfaces of the drum (slurry space, plates, etc.) to the horizontal line was determined. This result should also be taken into account for design of the separator drums for whey and its concentrates. The data obtained can be used for special whey separators elements design.